Flow-induced elongation of von Willebrand factor precedes tension-dependent activation - Hongxia Fu (Nature Portfolio, 2017)
Von Willebrand factor (VWF) is a blood protein involved in clotting and is proposed to be activated by flow, but the mechanism is unknown. Here the authors show that VWF is first converted from a compact to linear form by flow, and is subsequently activated to bind GPIbα in a tension-dependent manner.